Gevher Nesibe Sultan Hospital - Hayırlıdağ, Mustafa (Mehmet Ali YOLCU, 2021)
The Seljuk State in Anatolia continued its existence for about two centuries. During this time, Anatolia; it is equipped with many works such as darüşşifa, madrasah, mosque. Most of these works were inherited from the Anatolian geography and transferred to the Ottomans and then to today's Turkey. Although the existence of the medical school in Salerno is known, Gevher Nesibe Hospital has taken its place in the history scene since 1206 as both a medical school and a hospital. With its location on busy roads and its unique interior architecture, Darüşşifa has managed to be the center of attention in every era. The water and sound acoustics designed for mental patients are also in a size that can guide today's modern medicine approaches. It is important to examine the Gevher Nesibe Hatun Hospital in order to understand the medical education and medical approaches of the period. This study is an effort to make a note of history both in order to comprehend the Anatolian Seljuk understanding of medicine and to review the information about this structure, which has been inherited from the 13th century to all humanity. The contributions of fields such as the history of art, the history of architecture and the history of medicine are important in examining the works that have survived to the present day, such as the Gevher Nesibe Hospital.

Anadolu’da Selçuklu Devleti yaklaşık iki asır varlığını devam ettirmiştir. Bu zaman zarfında Anadolu; darüşşifa, medrese, camii gibi pek çok eserlerle donatılmıştır. Bu eserlerin çoğu miras olarak Anadolu coğrafyasında kalmış Osmanlılara ardından da günümüz Türkiye’sine intikal etmiştir. Salerno’daki tıp okulunun varlığı bilinmesine karşın hem tıp okulu hem de hastane hüviyetiyle Gevher Nesibe Darüşşifası 1206 yılından itibaren tarih sahnesindeki yerini almıştır. İşlek yollar üzerindeki konumu ve kendine has iç mimarisiyle Darüşşifa her devrin ilgi odağı olmayı başarmıştır. Akıl hastaları için kullanılan su ve ses akustiği de günümüz modern tıp yaklaşımlarına da rehberlik edebilecek boyuttadır. Dönemin tıp eğitimini ve tıbbi yaklaşımları anlamak açısından Gevher Nesibe Hatun Darüşşifası’nı incelemek önemlidir. Hem Anadolu Selçuklu tıp anlayışını kavramada hem de 13. yüzyıldan tüm insanlığa miras olarak kalan bu yapı hakkında bilgilerin gözden geçirilmesi adına bu çalışma, tarihe not düşme çabasıdır. Gevher Nesibe Darüşşifası gibi günümüze kadar gelebilmeyi başarabilmiş eserleri incelemede sanat tarihi, mimarlık tarihi ve tıp tarihi gibi alanların katkıları önem arz etmektedir.
Gevher Nesibe Sultan Darüşşifası